Analysis of genotype-by-environment interactions in a maize mapping population. Issue 3 (2nd February 2022) - Hudson, Asher I; Odell, Sarah G; Dubreuil, Pierre; Tixier, Marie-Helene; Praud, Sebastien; Runcie, Daniel E; Ross-Ibarra, Jeffrey
Abstract: Genotype-by-environment interactions are a significant challenge for crop breeding as well as being important for understanding the genetic basis of environmental adaptation. In this study, we analyzed genotype-by-environment interactions in a maize multiparent advanced generation intercross population grown across 5 environments. We found that genotype-by-environment interactions contributed as much as genotypic effects to the variation in some agronomically important traits. To understand how genetic correlations between traits change across environments, we estimated the genetic variance–covariance matrix in each environment. Changes in genetic covariances between traits across environments were common, even among traits that show low genotype-by-environment variance. We also performed a genome-wide association study to identify markers associated with genotype-by-environment interactions but found only a small number of significantly associated markers, possibly due to the highly polygenic nature of genotype-by-environment interactions in this population.